Characterisation of AMD pollution in the reservoirs of the Iberian Pyrite Belt - Grande, J. A. (2013)
A number of water-supply dams have been built in the semi-arid Iberian Pyrite Belt (SW Spain) in a ﬂuvial network affected by acid mine drainage (AMD). There are almost a hundred mines, most of which are closed, which emit low pH leachates with high metal and sulphate loads to reservoirs intended for urban supply. The Iberian Pyrite Belt contains 23 of these reservoirs spread along the Tinto and Odiel river basins, which are the main water courses affected by AMD, and the Chanza and the Guadiamar river basins, which are affected to a lesser extent. We characterised the degree of pollution in the various reservoirs that receive AMD-affected waters; this will eventually allow the development of a risk map of the overall extent of the problem in reservoirs in the Iberian Pyrite Belt.